The nexus between digitalization, entrepreneurial ecosystem quality, and economic resilience a cross-country analysis during the COVID-19 pandemic - Tan, Yeng-May; Autio, Erkko; Estrada, Gemma Esther B.; Park, Donghyun; Uddin, Gazi Salah (ADB Economics Working Paper Series)
Information and communication technology or digital technology helped entrepreneurs survive the coronavirus disease (COVID-19) restrictions. For instance, they shifted to online sales in the face of stringent lockdowns and mobility constraints. The enhanced resilience of entrepreneurs, in turn, contributed to the resilience of the broader economy. This study explores the relationship between the quality of a country’s digital entrepreneurial ecosystem, measured by the Global Index of Digital Entrepreneurship Systems (GIDES), and its economic performance during the COVID-19 pandemic. Based on a cross-country analysis of 100 global economies, we find a positive association between GIDES and economic performance during the pandemic. This suggests that the quality of a country’s environment for digital entrepreneurs can strengthen its economic resilience even in the face of major shocks.